(untitled) (Al-Academy, 2016)
The plant decorative arts field full of decorative Baltnoat from diversity in the design structure of vocabulary and whether units sepals, vase Aogsnah or written and what their catalog decorative hearts in Kadhimiya holy threshold of diversity in shapes and measurements and sizes.It is during the field visit of the researcher found that there are variations in the overall appearance and internal padding and this researcher has formulated the discussion by asking the following problem:(What is the diversity of designs decorative hearts in Kadhimiya holy threshold?)The importance of research in it:Research contributes to open the horizons of knowledge for researchers and scholars concerned with the teaching of the decorative arts, as well as promote closer cultural heritage and decorative facades Kadhimiya holy threshold.The research aims to:Reveal the diversity of designs decorative hearts in Kadhimiya holy threshold.As determined search internal and external interfaces as the current 1433 e 2012.This included the theoretical framework on the following topics:History sacred threshold of Kadhimiya, and the formal organization of the decorative hearts in Islamic art in terms of the diversity of the general appearance and internal padding diversity and color treatments.The researcher followed in their procedures descriptive approach to reach the results achieved its goals and solve the problem. The sample was selected in a way that Alvsidih if numbered (3) of the total sample (85) model and design tool (Form) and presented to the experts to make sure their validity, and the achievement of the Millennium.The search found results including:Accrediting divisions cadastral asymmetric and the emergence of hearts decorative Bhaoh formality with a dual function literacy, ornamental, as well as construction decorative according two methods (omnidirectional Omzdug) and varied movements including spiral and Lhalrkh rotational flipped, and showed finishes processing color antagonism hearts decorative between form and ground